Analisis Hubungan Motivasi dan Prestasi Belajar dalam Mata Pelajaran (IPS) Terpadu - Sulastri Sulastri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2019)
This study aims to determine the relationship between student motivation and student achievement. The researcher looked at several problems regarding learning motivation, in which 8th grade students at SMPN 2 Kec. Situjuah Limo Nagari is less motivated in learning on Integrated Social Sciences subjects and impacts on learning achievements such as Exercise scores, Pr, Daily Exams, Midterm Exams, and Final semester Exams. The type of research used is quantitative research with a correlation approach. The data collection techniques used by researchers include observation and questionnaires. The results of the study showed that based on the overall items of the questions obtained 3.31 This means that students' learning motivation is in good qualifications as expected. From the results of hypothesis testing and data processing there is a relationship between student learning motivation and student learning achievement so that the price coefficient obtained between x and y is 0.56 means in the medium category. Then it can be interpreted that the learning motivation of the 8th grade students at SMPN 2 Kec. Situjuah Limo Nagari is in a good level in supporting learning activities on the subject (IPS) Integrated so that it affects learning achievement. "There is a significant relationship between student learning motivation and learning achievement on Integrated (IPS) subjects at grade 8 at SMPN 2 Kec. Si Limo Nagari Academic Year 2018/2019" Accepted this means that there is a relationship between learning motivation and student achievement at SMPN 2 Kec. Situjuah Limo Nagari. From the results of this study concluded that student motivation is good and has a relationship between learning motivation and student achievement Keyword : Motivation Learning, Achievement Learning